1996
DOI: 10.1074/jbc.271.32.19421
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Changes and Stabilization of Inosine 5′-Monophosphate Dehydrogenase Associated with Ligand Binding and Inhibition by Mycophenolic Acid

Abstract: The effects of substrate, product, and inhibitor (mycophenolic acid) binding on the conformation and stability of hamster type II inosine 5-monophosphate dehydrogenase (IMPDH) have been examined. The protein in various states of ligand occupancy was compared by analyzing susceptibility to in vitro proteolysis, the degree of binding of a hydrophobic fluorescent dye, secondary structure content as determined by far-UV circular dichroism spectra, and urea-induced denaturation curves. These analysis methods reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 46 publications
(54 reference statements)
2
35
0
Order By: Relevance
“…Further, the presence of the SAD dinucleotide analogue may partially order the end of the active site flap, suggesting that the flap may stabilize both substrate and cofactor binding in the normal ternary complex. This is consistent with the observation that substrateinduced protection of the flap against proteolysis is enhanced by cofactor binding (66).…”
Section: Summary and Discussionsupporting
confidence: 80%
“…Further, the presence of the SAD dinucleotide analogue may partially order the end of the active site flap, suggesting that the flap may stabilize both substrate and cofactor binding in the normal ternary complex. This is consistent with the observation that substrateinduced protection of the flap against proteolysis is enhanced by cofactor binding (66).…”
Section: Summary and Discussionsupporting
confidence: 80%
“…Treatment with MPA results in the formation of large aggregates with a tendency to annular formation, although without the same level of definition found in intact cells. These data demonstrate that MPA causes self aggregation of IMPDH in the absence of other proteins or cellular elements, most likely through conformational change (20).…”
Section: Resultsmentioning
confidence: 88%
“…26 Later studies showed that binding of both IMP and NAD ϩ were required to induce a conformational rearrangement to produce a closed form of the enzyme. 27 After IMP and NAD ϩ are bound, IMP is oxidized to XMP*, a covalently bound intermediate. Once NADH leaves, MPA binds to form an inhibited complex with nanomolar affinity.…”
Section: Ligand Solution Structures By Transferred Noe Methodsmentioning
confidence: 99%